Apakah Inflasi Dapat Menurunkan Peningkatan Konsumsi Masyarakat Miskin Bukti Negara Berkembang Dan Maju Di Asia - Ghannili, Farawi (Cattleya Darmaya Fortuna, 2024)
Introduction/Main Objective: This study examines the impact of inflation, consumer price index (CPI) and consumer energy index (CEI) on poverty in developed and developing countries in Asia. This study aims to examine the impact of inflation on poverty by developing GLS and DGMM models. Background of the Problem: There is a relative influence in understanding inflation in increasing or decreasing the consumption of poor households in developed and developing countries in Asia, namely the strategic geographical location and income of the population of each country are different. Identification: each continuous variable and significantly in the DGMM model on poverty. Novelty: This paper not only focuses on inflation at the price level of goods but also focuses on the price level of energy consumption for the poor in developed and developing countries in Asia. Research Method: This study uses the Generalized Least Square and Difference Generalized Method of Moment models to examine and understand the state of poverty affected by inflation. Findings/Results: These findings reveal poverty as measured by household consumption affected by inflation in the price of goods and energy prices. This insight promises that price and energy inflation can increase or decrease the consumption of poor households. Conclusion: Continuously increasing inflation can directly benefit economic growth, but will be a problem for the poor in increasing their consumption.